Pengaruh Promosi Kesehatan Menggunakan Media Video Interaktif terhadap Kemampuan Hand Hygiene Pada Masyarakat Di Desa Soko Kabupaten Lamongan - Adindaru Lestari; Dadang Kusbiantoro; Arifal Aris (KOLONI, 2026)
Hand hygiene is a simple and effective practice to prevent the transmission of infectious diseases and improve public health. A preliminary survey conducted in Soko Village, Lamongan Regency, revealed that many community members were unable to perform the six-step hand hygiene procedure correctly. One strategy to improve this ability is health promotion using interactive video media, which presents educational material in an attractive, clear, and easy-to-understand format. This study aimed to determine the effect of health promotion through interactive video media on the hand hygiene ability of the community in Soko Village, Lamongan Regency. This study employed a pre-experimental design with a one-group pre-test and post-test approach. The population consisted of 84 people, and 70 respondents were selected using purposive sampling. The intervention was conducted over three weeks. Data were collected using a hand hygiene ability questionnaire and analyzed with the Wilcoxon test because the data were not normally distributed. The results showed that the mean pre-test score before the intervention was 2.87 and improved to 1.77 in the third-week post-test. The Wilcoxon test showed significant differences in the first week (p=0.001), second week (p=0.000), and third week (p=0.000), indicating that interactive video-based health promotion significantly improved the community's hand hygiene ability.